2022
DOI: 10.29333/ejmste/12160
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics teachers’ conceptual understanding of soft skills in secondary schools in Zambia

Abstract: Teachers' conceptual knowledge contributes to the quality of teaching and learning of mathematics. The purpose of this study was to explore how mathematics teachers show understanding of soft skills and if they are aware of the methods that incorporate them in teaching and learning of mathematics. The sample consisted of 91 mathematics teachers, comprising 48 males and 43 females, who were purposively selected from secondary schools in Mazabuka district in Zambia. The parallel mixed design was used to collect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…HLT is a conjecture flow of students' thoughts in studying a topic, can show the interplay between activities and the learning process (Pamungkas et al, 2020). Various research results use HLT to improve students' conceptual understanding skills (Busaka et al, 2022). The preparation of HLT is the final part of the learning reflection process carried out by the teacher/lecturer.…”
Section: Resultsmentioning
confidence: 99%
“…HLT is a conjecture flow of students' thoughts in studying a topic, can show the interplay between activities and the learning process (Pamungkas et al, 2020). Various research results use HLT to improve students' conceptual understanding skills (Busaka et al, 2022). The preparation of HLT is the final part of the learning reflection process carried out by the teacher/lecturer.…”
Section: Resultsmentioning
confidence: 99%
“…Frontiers in Education 07 frontiersin.org of soft skills, and most were unaware of the methods and assessment strategies that incorporate soft skills (Busaka et al, 2022). Mukuka et al (2021) suggested that mathematics self-efficacy and task-specific selfefficacy beliefs collectively and significantly can mediate the effect of the instructional approach on mathematical reasoning.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Algebra merupakan salah satu bidang pembelajaran dalam matematik di Malaysia. Kebolehan penyelesaian algebra bagi abad ke-21 lebih menekankan pemahaman dan pengaplikasian konsep algebra untuk menganalisis, mengitlakkan dan mewakilkan sesuatu situasi masalah yang mempunyai pelbagai jalan penyelesaian (Rizki & Priatna, 2018;Szabo et al, 2020) bukan lagi sebagai satu disiplin yang melibatkan proses memanipulasi simbol, penghafalan langkah penyelesaian untuk mendapat satu jawapan (Busaka et al, 2022;Wijesundera et al, 2023). Jika dilihat dari pencapaian dalam TIMSS 2007-2019 mengikut domain kandungan iaitu nombor, algebra, geometri, dan data dan kebarangkalian, pencapaian dalam algebra menunjukkan tren pencapaian yang meningkat tetapi jika dibandingkan mengikut domain kandungan, pencapaian dalam algebra agak rendah berbanding yang lain (Kementerian Pendidikan Malaysia, 2020).…”
Section: Pengenalanunclassified